Multi sensor based smart medical ring for health monitoring system. Issue 1 (1st July 2022) - Paul, Bidisha; Chakraborty, Bishal; Dhar, Abhishek; Adhikari, Saurabh; Saha, Sourav; Biswas, Papun; Das, Partha; Das, Sudip; Pal, Biswamoy; Ray, Partha; Sasmal, Milan
Abstract: Now a days the smart device put a huge impact on medical field rapidly. In 20 st century everyone concerns about their health to fight with this pandemic. A smart medical ring has been discovered to ensure proper treatment of some health issues. There are so many devices available in the wearable technology market like smart watch, smart mask etc. This device will help to measure the temperature, oxygen level andpulse rate all together. Objective of this project is to combine the features of thermometer and pulse oximeter into a single device with a reducible size compare to other available devices so that anyone can use this device in any place at any time and also can wear the ring in his/her finger. Here two sensors are implemented to measure these three different parameters. The thermometer and the pulse oximeter are most required measuring tools in our daily life to check the common health parameters. That's why this smart medical ring has been discovered by the researchers to help the common people and medical field.